Serial analysis of cardiopulmonary fitness and echocardiography in patients with Fabry disease undergoing enzyme replacement therapy - Tuan, S; Chiu, P; Liou, I; Lu, W; Huang, H; Wu, S; Chen, G; Lin, K (Journal of rehabilitation medicine. Clinical communications, 2020)
Fabry disease, a rare X-linked disorder, can lead to exercise intolerance. In Taiwan, the cardiac variant of Fabry disease has a significantly higher prevalence than the classic variant. The cardiac variant of Fabry disease primarily involves the heart. Enzyme replacement therapy has been used to treat both variants. We aimed to study the impact of enzyme replacement therapy on exercise and cardiac structures between the classic (CL-FD) and cardiac variant (CV-FD) Fabry disease. Retrospective analysis of 2 groups of patients with Fabry disease (5 patients with the classic variant and 5 with the cardiac variant), who were undergoing enzyme replacement therapy. Patients were assessed annually for 3 years using symptom-limited cycle ergometry and echocardiography. Subjects were 5 women, mean age 53 (standard deviation (SD) 14.05) years with CL-FD Fabry disease, and 5 men, mean age 65 (SD 2.35) years with CV-FD. The percentage of peak oxygen consumption to predicted value for all included patients was significantly lower (78.78% (SD 12.72)) than 100%. Annual serial measurement showed that peak metabolic equivalent and percentage of peak oxygen consumptiondecreased significantly over a period of 3 years in patients with CV-FD ( = 0.002, and =0.004, respectively), but not in those with CL-FD. There were no significant changes in annual serial measurements of left ventricular mass or interventricular septal thickness in patients with either variant of Fabry disease over a period of 3 years. Peak exercise capacity of the patients with Fabry disease was lower than that of normal peers. Peak exercise capacity decreased over time.